2017
DOI: 10.1016/j.bjorl.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 419 patients with acquired middle ear cholesteatoma

Abstract: The prevalence of cholesteatoma in patients with chronic otitis media was 24.5% and it was more common in adults than in children. Posterior mesotympanic cholesteatoma was more frequent, with no difference in mean air-bone gap between the different routes of formation. In patients undergoing surgery, open tympanomastoidectomy was the procedure most frequently chosen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…An important contributing factor for auditory tubal dysfunction is the mechanical obstruction caused by adenotonsillar hypertrophy, which can deregulate the pressure in the middle ear cavity 19 . This was supported by a prospective cohort study of 1710 patients with chronic otitis media, which revealed that nearly 25% developed cholesteatomas 7 . The improvement of otitis media with effusion (OME) post adenoidectomy in children suggests that adenoids may act as reservoirs of microbial infections 20‐23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important contributing factor for auditory tubal dysfunction is the mechanical obstruction caused by adenotonsillar hypertrophy, which can deregulate the pressure in the middle ear cavity 19 . This was supported by a prospective cohort study of 1710 patients with chronic otitis media, which revealed that nearly 25% developed cholesteatomas 7 . The improvement of otitis media with effusion (OME) post adenoidectomy in children suggests that adenoids may act as reservoirs of microbial infections 20‐23 .…”
Section: Discussionmentioning
confidence: 99%
“…19 This was supported by a prospective cohort study of 1710 patients with chronic otitis media, which revealed that nearly 25% developed cholesteatomas. 7 The improvement of otitis media with effusion (OME) post adenoidectomy in children suggests that adenoids may act as reservoirs of microbial infections. [20][21][22][23] In studies of colonization of adenotonsillar tissues by bacteria and viruses, multiple pathogens were detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of a questionnaire or the systematic questioning of patients regarding their symptoms does not yet appear to be general practice. The national cholesteatoma study and the literature ( 16 , 17 ) show that hearing loss with or without otorrhea is the most important health concern. In addition, to improve hearing, the cessation of otorrhea is a determining factor for the success of surgery according to patients.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain a better understanding of outcome measures that are important for patients, a list of the most frequently reported symptoms (both pre- and postoperative) was drawn up from the literature ( 16 19 ). This information was combined with the information on overall patients’ symptoms taken from the national Dutch Cholesteatoma Data study (DCD) (trial 80-83700-98-16504).…”
Section: Methodsmentioning
confidence: 99%